Neoadjuvant immunotherapy for resectable esophageal cancer: A review - Li, Qing; Liu, Ting; Ding, Zhenyu (Frontiers in Immunology, 2022)
Esophageal cancer (EC) is one of the most common cancers worldwide, especially in China. Despite therapeutic advances, the 5-year survival rate of EC is still dismal. For patients with resectable disease, neoadjuvant chemoradiotherapy (nCRT) in combination with esophagectomy is the mainstay of treatment. However, the pathological complete response (pCR) rate to nCRT of 29.2% to 43.2% is not satisfactory, and approximately half of the patients will develop either a locoregional recurrence or distant metastasis. It is, therefore, necessary to explore novel and effective treatment strategies to improve the clinical efficacy of treatment. Immunotherapy utilizing immune checkpoint inhibitors (ICIs) has significantly changed the treatment paradigm for a wide variety of advanced cancers, including EC. More recently, increasing clinical evidence has demonstrated that neoadjuvant immunotherapy can potentially improve the survival of patients with resectable cancers. Furthermore, accumulating findings support the idea that chemotherapy and/or radiotherapy can activate the immune system through a variety of mechanisms, so a combination of chemotherapy and/or radiotherapy with immunotherapy can have a synergistic antitumor effect. Therefore, it is reasonable to evaluate the role of neoadjuvant immunotherapy for patients with surgically resectable EC. In this review, we discuss the rationale for neoadjuvant immunotherapy in patients with EC, summarize the current results of utilizing this strategy, review the planned and ongoing studies, and highlight the challenges and future research needs.